Ti3C2 / WO3 Schottky heterojunction photoanode and preparation method and application thereof

By adopting Ti3C2/WO3 Schottky heterojunction photoanode, the problem of slow oxygen precipitation reaction rate in photoelectrocatalytic water decomposition is solved, and the photoelectrocatalytic performance and reaction efficiency are significantly improved.

CN119506956AActive Publication Date: 2025-02-25HENAN UNIVERSITY

Patent Information

Application Number
CN202411609711.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-12
Publication Date
2025-02-25
Estimated Expiration
2044-11-12

AI Technical Summary

Technical Problem

In the existing photoelectric catalytic water decomposition, the rate of oxygen precipitation reaction is slow, which affects the overall reaction efficiency. In particular, the problem of WO3 materials having a faster carrier recombination rate limits its development.

Method used

A Ti3C2/WO3 Schottky heterojunction photoanode was used to coat the Ti3C2 dispersion and tungstate acid mixed solution on the conductive glass, and prepared by hydrothermal reaction and high-temperature calcination to form a photoanode composed of Ti3C2 square nanoparticles and a layer of inlaid WO3 nanosheets.

Benefits of technology

The carrier recombination rate in oxide semiconductors is significantly reduced, the photoelectric catalytic water decomposition performance is improved, the photocurrent reaches twice that of the pure WO3 photoanode at 1.23V voltage, and the electrochemical reaction resistance Rct is significantly reduced.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119506956A_ABST
    Figure CN119506956A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of photoelectric materials, and particularly relates to a Ti3C2 / WO3 Schottky heterojunction photoanode and a preparation method and application thereof. The preparation method of the photo-anode comprises the following steps: (1) coating a Ti3C2 dispersion liquid on a conductive surface of pretreated conductive glass to obtain conductive glass with a Ti3C2 layer on the surface; (2) coating a tungstic acid mixed solution on the Ti3C2 layer, and drying to obtain conductive glass with tungstic acid / Ti3C2 on the surface; and (3) putting the conductive glass with the tungstic acid / Ti3C2 on the surface into a precursor solution for growing WO3 in a manner that the conductive surface faces downwards to carry out hydrothermal reaction, and then cleaning, drying and calcining to obtain the Ti3C2 / WO3 Schottky heterojunction photo-anode. The Schottky heterojunction photo-anode prepared by the method can promote the separation of photon-generated carriers, so that the photoelectrocatalysis performance is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of optoelectronic materials, and in particular relates to a Ti3C2 / WO3 Schottky heterojunction photoanode and a preparation method and application thereof. Background Art

[0002] Faced with increasingly severe environmental problems caused by the development of extensive fossil energy consumption, people are urgently developing and utilizing clean and sustainable energy, and hydrogen energy has gained widespread attention due to its extremely high energy density and completely clean products. However, among the complex hydrogen production methods, photoelectrocatalysis (PEC) water decomposition has attracted much attention due to its clean, environmentally friendly, renewable, and convenient characteristics. Compared with the hydrogen evolution reaction (HER) on the cathode side, the oxygen evolution reaction (Oxygen Evolution Reaction, OER) on the anode side has a slow reaction rate and is also a key step in the photoelectrocatalytic water decomposition reaction. Therefore, the selection of semiconductor materials with suitable bandgap width (Energy gap, Eg) and how to improve the catalytic activity of photoelectrocatalysts have become urgent issues to be solved in photoelectrocatalytic water decomposition.

[0003] A variety of oxide materials such as Fe2O3, BiVO4, Ag3PO4, WO3, ZnO, TiO2 and other semiconductor materials have been proven to be successfully used in the process of photoelectrocatalytic water splitting. However, materials such as ZnO (Eg = 3.0 ~ 3.4eV) and TiO2 (Eg = 3.0 ~ 3.2eV) have a large bandgap and cannot produce light response in the visible light range; although materials such as BiVO4 and Ag3PO4 have more suitable Eg, they are limited by factors such as cumbersome synthesis process and material stability; and WO3 has become one of the popular materials in the field of photoelectrocatalysis because of its bandgap of 2.5 ~ 2.9eV, low synthesis cost and environmental friendliness. However, WO3 itself still has problems such as fast carrier recombination rate, which limits its development in the field of photoelectrocatalytic water splitting, so appropriate solutions are needed to implement it.

[0004] Ti3C2 is a kind of emerging material of two-dimensional transition metal nitrogen carbon compound MXene. It can be used as a co-catalyst in the field of photoelectrocatalysis due to its excellent mechanical properties and high conductivity of metal-like properties. Compared with precious metal co-catalysts (such as Au, Pd, Pt, etc.) and transition metals, Ti3C2 has low cost and no pollution. The introduction of co-catalysts between the substrate and the oxide semiconductor material can form a Schottky heterojunction with the oxide semiconductor, accelerate electron transmission, and thus significantly reduce the carrier recombination rate in the oxide semiconductor, thereby improving its photoelectrocatalytic performance. Based on this, the present invention provides a new photoanode for photoelectrocatalytic water decomposition to improve the photoelectrocatalytic performance. Summary of the invention

[0005] One of the purposes of the present invention is to provide a method for preparing a Ti3C2 / WO3 Schottky heterojunction photoanode, which is easy to operate.

[0006] A second object of the present invention is to provide a Ti3C2 / WO3 Schottky heterojunction photoanode that can improve photoelectrocatalytic performance.

[0007] The third object of the present invention is to provide an application of a Ti3C2 / WO3 Schottky heterojunction photoanode, which has broad application prospects.

[0008] One of the purposes of the present invention is achieved by the following technical solution:

[0009] A method for preparing a Ti3C2 / WO3 Schottky heterojunction photoanode comprises the following steps:

[0010] (1) coating a Ti3C2 dispersion on the conductive surface of the pretreated conductive glass to obtain a conductive glass having a Ti3C2 layer on the surface;

[0011] (2) coating a tungstic acid mixed solution on the Ti3C2 layer, and obtaining a conductive glass having tungstic acid / Ti3C2 on the surface after drying;

[0012] (3) placing the conductive glass with tungstic acid / Ti3C2 on the surface with the conductive surface facing downward in a precursor solution for growing WO3 for hydrothermal reaction, and then washing, drying and calcining to obtain a Ti3C2 / WO3 Schottky heterojunction photoanode.

[0013] Furthermore, in the Ti3C2 / WO3 Schottky heterojunction photoanode in step (3), the mass ratio of WO3 to Ti3C2 is 1:(0.1-0.2); and the concentration of the Ti3C2 dispersion is 1-3 mg / mL.

[0014] Furthermore, the preparation method of the tungstic acid mixed solution is: dissolving sodium metatungstate in water, then adding citric acid and hydrochloric acid and stirring; after the preparation, the concentrations of sodium metatungstate, citric acid and hydrochloric acid are 3-5 mg / mL, 7-10 mg / mL and 0.8-1.0 mol / L.

[0015] Furthermore, the preparation method of the precursor solution is: dissolving sodium metatungstate and citric acid in water, then adding hydrochloric acid and stirring, and after the preparation, the concentrations of sodium metatungstate, citric acid and hydrochloric acid in the solution are 3-5 mg / mL, 7-10 mg / mL and 0.2-0.5 mol / L.

[0016] Furthermore, the method of coating the Ti3C2 dispersion in step (1) is multi-step spin coating, the method is: first spin coating the Ti3C2 dispersion at 450-550rpm for 18-22s, and then spin coating at 2900-3100rpm for 38-42s; the method of coating the tungstic acid mixed solution in step (2) is: spin coating at 2900-3100rpm for 18-22s.

[0017] Multi-step spin coating is divided into two processes: slow spin coating is to make the Ti3C2 solution on FTO spread more evenly and adsorb more thoroughly; fast spin coating is to separate the Ti3C2 solution that is not adsorbed on the FTO surface from the surface, reduce the volume of the solution, and thus shorten the transmission path required for electrons and accelerate the separation of electrons and holes.

[0018] Furthermore, the temperature of the hydrothermal reaction in step (2) is 110-130°C, and the time is 10-13h. The temperature of the calcination in step (2) is 400-600°C, and the time is 2-5h; and the calcination is carried out in air.

[0019] Furthermore, in step (2), the temperature of the hydrothermal reaction is 120° C. and the time is 12 h; the temperature of the calcination is 500° C. and the time is 3 h.

[0020] Furthermore, the heating rate to the calcination temperature is 4-10°C / min.

[0021] Furthermore, the heating rate of the calcination temperature is 5°C / min.

[0022] Furthermore, the conductive glass in step (1) is FTO conductive glass or ITO conductive glass.

[0023] Furthermore, the pretreatment in step (1) includes: placing the conductive glass in a mixture of deionized water and ethanol, and a mixture of 30% hydrogen peroxide and concentrated sulfuric acid in sequence for cleaning, and drying after cleaning to obtain the pretreated conductive glass.

[0024] Furthermore, the volume ratio of the deionized water to the ethanol is 1:1-1.5, and the volume ratio of the 30% hydrogen peroxide to the concentrated sulfuric acid is 3-4:1; the conductive glass is ultrasonically cleaned in the mixture of deionized water and ethanol for 25-30 minutes, and immersed in the mixture of 30% hydrogen peroxide and concentrated sulfuric acid for 15-20 minutes.

[0025] The present invention firstly adopts a mixed solution of deionized water and ethanol to ultrasonically clean the pollutants such as dust on the surface of the FTO transparent substrate, and then uses a mixed solution of hydrogen peroxide and concentrated sulfuric acid to soak and clean the organic matter attached to the FTO surface and etch the conductive coating to increase its hydrophilicity, which is beneficial to the adhesion of Ti3C2 dispersion and the growth of WO3.

[0026] The second object of the present invention is achieved by adopting the following technical solution:

[0027] A Schottky heterojunction photoanode is prepared by using the above preparation method.

[0028] The third object of the present invention is achieved by adopting the following technical solution:

[0029] The above-mentioned Schottky heterojunction photoanode is used in the photoelectrocatalytic water decomposition reaction.

[0030] Compared with the prior art, the beneficial effects of the present invention are mainly:

[0031] 1. The present invention first spin-coats a Ti3C2 dispersion on the surface of a conductive glass in multiple steps, then spin-coats a tungstic acid mixed solution in a single step, and then calcines the mixture in a muffle furnace in an air atmosphere at high temperature after a hydrothermal reaction and drying, thereby finally obtaining a sheet-like Ti3C2 / WO3 photoanode with a Schottky heterojunction, wherein the photoanode is composed of Ti3C2 square nanoparticles and WO3 nanosheets embedded on the nanoparticles. The preparation method of the Ti3C2 / WO3 photoanode of the present invention has simple steps and simple operation, and has the prospect of large-scale commercial production.

[0032] 2. Ti3C2 is introduced into the Schottky heterojunction photoanode of the present invention. The introduction of Ti3C2 can significantly accelerate the surface charge reaction transmission process, thereby promoting the separation of photogenerated carriers and accelerating the reaction process. In addition, the Schottky heterojunction photoanode of the present invention also has a matching Fermi level position, so that after Ti3C2 and WO3 in the system contact, the electron transition from Ti3C2 to WO3 forms a built-in electric field, thereby significantly improving the photoelectrocatalytic water decomposition performance.

[0033] 3. The photocurrent generated by the Ti3C2 / WO3 photoanode of the present invention at a voltage of 1.23V is about twice that of the pure WO3 photoanode, and the electrochemical reaction resistance Rct is significantly reduced by about 400Ω. The device quality is stable and has potential prospects for large-scale production, providing new ideas for the construction of photoanodes. BRIEF DESCRIPTION OF THE DRAWINGS

[0034] Figure 1 This is a SEM image of the Ti3C2 / WO3 Schottky heterojunction photoanode of Example 1 of the present invention;

[0035] Figure 2 This is the XRD diagram of the Ti3C2 / WO3 Schottky heterojunction photoanode of Example 1 of the present invention;

[0036] Figure 3 FT-IR image of the Ti3C2 / WO3 Schottky heterojunction photoanode of Example 1 of the present invention;

[0037] Figure 4 This is the full XPS spectrum of the Ti3C2 / WO3 Schottky heterojunction photoanode of Example 1 of the present invention;

[0038] Figure 5 This is the W 4f fine spectrum of the Ti3C2 / WO3 Schottky heterojunction photoanode in Example 1 of the present invention;

[0039] Figure 6 This is a JV curve diagram of the Ti3C2 / WO3 Schottky heterojunction photoanode of Example 1 of the present invention;

[0040] Figure 7 This is the Nyquist diagram of the Ti3C2 / WO3 Schottky heterojunction photoanode according to Example 1 of the present invention. DETAILED DESCRIPTION

[0041] The following is a further detailed description of the present invention in conjunction with specific preferred embodiments, and it cannot be determined that the specific implementation of the present invention is limited to these descriptions. For those of ordinary skill in the technical field to which the present invention belongs, without departing from the concept of the present invention, several simple deductions or replacements can also be made, all of which should be deemed to belong to the protection scope of the present invention. The specific conditions not indicated in the embodiments are carried out according to conventional conditions or conditions recommended by the manufacturer. The reagents or instruments used, unless otherwise specified, are conventional products obtained through commercial channels.

[0042] Among them, the relevant parameters of the FTO conductive glass in the embodiment are as follows:

[0043] The thickness is 2.2mm, the square resistance is 6~8Ω, the transmittance is higher than 78%, and it can withstand high temperatures of 600℃.

[0044] The relevant parameters of ITO conductive glass are as follows:

[0045] The thickness is 1.1mm, the square resistance is 12~18Ω, the transmittance is about 90%, and it can withstand high temperatures of 500℃.

[0046] (I) Embodiment

[0047] Example 1

[0048] This embodiment provides a method for preparing a Ti3C2 / WO3 Schottky heterojunction photoanode, and the specific preparation process is as follows:

[0049] Prepare tungstic acid mixed solution: weigh 0.093g sodium metatungstate, put it in a beaker and add 12mL deionized water to stir and dissolve. After dissolution, add 2mL of 36% concentrated hydrochloric acid (11.7mol / L) solution and continue stirring; weigh 0.196g citric acid, add it to the above solution and add 13mL deionized water, stir at 800rpm until it is translucent to obtain a tungstic acid mixed solution for use.

[0050] Prepare the precursor solution: weigh 0.093g sodium metatungstate and 0.196g citric acid into a beaker and add 25mL deionized water to stir and dissolve, then drop 2mL of 3mol / L hydrochloric acid solution and continue stirring for 20min to obtain the precursor solution for later use.

[0051] (1) The FTO conductive glass was immersed in an ethanol aqueous solution, wherein the mass ratio of deionized water to anhydrous ethanol in the ethanol aqueous solution was 1:1.2, and ultrasonic treatment was performed for 25 minutes. Then, the ultrasonically treated FTO conductive glass was immersed in a mixed solution of hydrogen peroxide and concentrated sulfuric acid for 18 minutes, wherein the mass fraction of hydrogen peroxide in the mixed solution was 30%, and the volume ratio of hydrogen peroxide to concentrated sulfuric acid was 3:1. Then, the FTO conductive glass was repeatedly rinsed with an ethanol aqueous solution (the mass ratio of deionized water to anhydrous ethanol in the ethanol aqueous solution was 1:1.2), and blown dry with high-purity nitrogen gas with a purity of 99.999%, to obtain a pretreated FTO conductive glass.

[0052] The pretreated FTO conductive glass was placed in a gelling machine and adsorbed under negative pressure. 200 μL of 2 mg / mL Ti3C2 dispersion was taken and spin-coated on the conductive surface of the FTO conductive glass by multi-step spin coating. The multi-step spin coating program was set at 500 rpm·s -1 The rotation speed was increased by acceleration, increased to 500 rpm after 1 second and maintained for 20 seconds, then increased to 3000 rpm after 5 seconds and maintained for 40 seconds, and dried on a heating table at 80°C. After drying, the conductive glass was placed in an ozone cleaner for 30 minutes to obtain a conductive glass with a Ti3C2 layer on the surface.

[0053] (2) Take 100 μL of the above tungstic acid mixed solution and spin-coat the tungstic acid mixed solution on the Ti3C2 layer by single-step spin coating. The single-step spin coating setting program is 500 rpm·s -1 The speed was accelerated and increased to 3000 rpm after 6 s and maintained for 20 s, and dried on a heating table at 80°C to obtain a conductive glass with tungstic acid / Ti3C2 on the surface.

[0054] Take 35mL of the above precursor solution and add it to a polytetrafluoroethylene reactor, then place the conductive glass with tungstic acid / Ti3C2 on the surface with the conductive surface facing down in the polytetrafluoroethylene reactor, and carry out hydrothermal reaction at 120°C for 12h. After the reaction is completed, take it out after naturally cooling to room temperature, rinse it with ethanol, and blow dry it with high-purity nitrogen with a purity of 99.999%. The dried substrate is placed in a muffle furnace, heated to 500°C at a heating rate of 5°C / min, and calcined for 3h to obtain a Ti3C2 / WO3 Schottky heterojunction photoanode.

[0055] Example 2

[0056] This embodiment provides a method for preparing a Schottky heterojunction photoanode, and the specific preparation process is as follows:

[0057] Prepare tungstic acid mixed solution: weigh 0.175g sodium metatungstate, put it in a beaker and add 14mL deionized water to stir and dissolve. After dissolution, add 3mL of 37% concentrated hydrochloric acid solution (12.1mol / L) and continue stirring; weigh 0.35g citric acid, add it to the above solution and add 18mL deionized water, stir at 800rpm until it is translucent to obtain a tungstic acid mixed solution for use.

[0058] Prepare the precursor solution: weigh 0.17g sodium metatungstate and 0.35g citric acid into a beaker and add 32.5mL deionized water to stir and dissolve, add 2.5mL 3mol / L hydrochloric acid solution and continue stirring for 20min to obtain the precursor solution for later use.

[0059] (1) ITO conductive glass is immersed in an ethanol aqueous solution, wherein the mass ratio of deionized water to anhydrous ethanol in the ethanol aqueous solution is 1:1, and ultrasonic treatment is performed for 20 minutes. Then, the ultrasonically treated ITO conductive glass is immersed in a mixed solution of hydrogen peroxide and concentrated sulfuric acid for 10 minutes, wherein the mass fraction of hydrogen peroxide in the mixed solution is 30%, and the volume ratio of hydrogen peroxide to concentrated sulfuric acid is 4:1. Then, the ITO conductive glass is repeatedly rinsed with an ethanol aqueous solution (the mass ratio of deionized water to anhydrous ethanol in the ethanol aqueous solution is 1:1), and high-purity nitrogen gas with a purity of 99.999% is used for blowing and drying to obtain a pretreated ITO conductive glass.

[0060] The pretreated ITO conductive glass was placed in a coating machine and adsorbed under negative pressure. 200 μL of 1 mg / mL Ti3C2 dispersion was taken and spin-coated on the conductive surface of the ITO conductive glass by multi-step spin coating. The multi-step spin coating program was set at 500 rpm·s -1The rotation speed was increased by acceleration, increased to 500 rpm after 1 second and maintained for 20 seconds, then increased to 3000 rpm after 5 seconds and maintained for 40 seconds, and dried on a heating table at 80°C. After drying, the substrate was placed in an ozone cleaner for 30 minutes to obtain a conductive glass with a Ti3C2 layer on the surface.

[0061] (2) Take 100 μL of the above tungstic acid mixed solution and spin-coat the tungstic acid mixed solution on the Ti3C2 layer by single-step spin coating. The single-step spin coating setting program is 500 rpm·s -1 The speed was accelerated and increased to 3000 rpm after 6 s and maintained for 20 s, and dried on a heating table at 80°C to obtain a conductive glass with tungstic acid / Ti3C2 on the surface.

[0062] Take 35mL of the above precursor solution and add it to a polytetrafluoroethylene reactor, then place the above conductive glass with tungstic acid / Ti3C2 on the surface with the conductive surface facing down in the polytetrafluoroethylene reactor, and carry out hydrothermal reaction at 130°C for 10 hours. After the reaction is completed, take it out after naturally cooling to room temperature, rinse it with ethanol, and blow dry it with high-purity nitrogen with a purity of 99.999%. The dried substrate is placed in a muffle furnace, heated to 600°C at a heating rate of 4°C / min, and calcined for 2 hours to obtain a Ti3C2 / WO3 Schottky heterojunction photoanode.

[0063] Example 3

[0064] This embodiment provides a method for preparing a Schottky heterojunction photoanode, and the specific preparation process is as follows:

[0065] Prepare tungstic acid mixed solution: weigh 0.12g sodium metatungstate, put it in a beaker and add 17.5mL deionized water to stir and dissolve. After dissolution, add 2.5mL of 38% concentrated hydrochloric acid solution (12.4mol / L) and continue stirring; weigh 0.28g citric acid, add it to the above solution and add 20mL deionized water, stir at 800rpm until it is translucent to obtain a tungstic acid mixed solution for use.

[0066] Prepare the precursor solution: weigh 0.12g sodium metatungstate and 0.28g citric acid into a beaker and add 38mL deionized water to stir and dissolve, then drop 2mL of 4mol / L hydrochloric acid solution and continue stirring for 20min to obtain the precursor solution for later use.

[0067] (1) The FTO conductive glass was immersed in an ethanol aqueous solution, wherein the mass ratio of deionized water to anhydrous ethanol in the ethanol aqueous solution was 1:1.5, and ultrasonic treatment was performed for 30 minutes. Then, the ultrasonically treated FTO conductive glass was immersed in a mixed solution of hydrogen peroxide and concentrated sulfuric acid for 20 minutes, wherein the mass fraction of hydrogen peroxide in the mixed solution was 30%, and the volume ratio of hydrogen peroxide to concentrated sulfuric acid was 3:1. Then, the FTO transparent substrate was repeatedly rinsed with an ethanol aqueous solution (the mass ratio of deionized water to anhydrous ethanol in the ethanol aqueous solution was 1:1.5), and blown dry with high-purity nitrogen gas with a purity of 99.999%, to obtain a pretreated FTO conductive glass.

[0068] The pretreated FTO conductive glass was placed in a gelling machine and adsorbed under negative pressure. 200 μL of 3 mg / mL Ti3C2 dispersion was taken and spin-coated on the conductive surface of the FTO conductive glass by multi-step spin coating. The multi-step spin coating program was set at 500 rpm·s -1 The rotation speed was increased by acceleration, increased to 500 rpm after 1 second and maintained for 20 seconds, then increased to 3000 rpm after 5 seconds and maintained for 40 seconds, and dried on a heating table at 80°C. After drying, the substrate was placed in an ozone cleaner for 30 minutes to obtain a conductive glass with a Ti3C2 layer on the surface.

[0069] (2) Take 100 μL of the above tungstic acid mixed solution and spin-coat the tungstic acid mixed solution on the Ti3C2 layer by single-step spin coating. The single-step spin coating setting program is 500 rpm·s -1 The speed was accelerated and increased to 3000 rpm after 6 s and maintained for 20 s, and dried on a heating table at 80°C to obtain a conductive glass with tungstic acid / Ti3C2 on the surface.

[0070] Take 35mL of the above precursor solution and add it to a polytetrafluoroethylene reactor, then place the conductive surface of the conductive glass with tungstic acid / Ti3C2 on the surface face down in the polytetrafluoroethylene reactor, and carry out hydrothermal reaction at 110°C for 13h. After the reaction is completed, take it out after naturally cooling to room temperature, rinse it with ethanol, and blow dry it with high-purity nitrogen with a purity of 99.999%. The dried substrate is placed in a muffle furnace, heated to 400°C at a heating rate of 10°C / min, and calcined for 5h to obtain the Ti3C2 / WO3 Schottky heterojunction photoanode.

[0071] (II) Comparative Example

[0072] Comparative Example 1 provides a pure WO3 photoanode, which is different from Example 1 in that: Ti3C2 dispersion is not coated in step (1), and the rest is the same as Example 1.

[0073] (III) Product structure characterization and performance testing

[0074] The structure and application of the Schottky heterojunction photoanode provided in the embodiments of the present invention are described in detail below.

[0075] 1. Microstructure of Ti3C2 / WO3 Schottky heterojunction photoanode

[0076] The top view of the microstructure of the Ti3C2 / WO3 Schottky heterojunction photoanode in Example 1 was observed by scanning electron microscopy (SEM). Figure 1 .

[0077] Figure 1 This is the SEM image of the Ti3C2 / WO3 Schottky heterojunction photoanode of Example 1. Figure 1 It can be seen that the Schottky heterojunction photoanode is composed of Ti3C2 square nanoparticles and WO3 nanosheets embedded on the nanoparticles.

[0078] 2. Crystal structure of WO3 in Ti3C2 / WO3 Schottky heterojunction photoanode

[0079] The crystal structures of WO3 in the Ti3C2 / WO3 Schottky heterojunction photoanode of Example 1 and WO3 photoanode of Comparative Example 1 were observed by X-ray diffractometer. Figure 2 .

[0080] Figure 2 The XRD pattern of the Schottky heterojunction photoanode of Example 1. Among them, 2θ=23.1°, 23.6°, 24.2°, 54.7° and 54.9° correspond to the (001), (020), (200), (401) and (420) crystal planes in the simple orthorhombic phase WO3 (PDF#00-020-1324), respectively, which have been marked with triangle symbols in the figure; 2θ=26.8°, 37.8°, 51.6° can be classified as the peaks of F-doped SnO2 on the surface of the FTO transparent substrate, and the Ti3C2 material has no obvious diffraction peaks in XRD.

[0081] 3. Composition of Ti3C2 / WO3 Schottky heterojunction photoanode

[0082] The composition of the Ti3C2 / WO3 Schottky heterojunction photoanode of Example 1 was detected by Fourier transform infrared spectroscopy FT-IR. The results are as follows: Figure 3 shown.

[0083] Figure 3 This is the FT-IR spectrum of the Ti3C2 / WO3 Schottky heterojunction photoanode in Example 1. Figure 3 The wave number is 820 cm -1 、770cm -1 、663cm -1The points correspond to the bending vibration absorption peaks of the WO bond and WOW bond of WO3 and the bending vibration absorption peak of the Ti-O bond formed after ozonation treatment of Ti3C2, which proves the existence of trace amounts of Ti3C2 combined with WO3.

[0084] 4. Proportion of WO3 and Ti3C2 in Ti3C2 / WO3 Schottky heterojunction photoanode

[0085] XPS was used to detect the proportion of WO3 and Ti3C2 in the Ti3C2 / WO3 Schottky heterojunction photoanode of Example 1. The results are as follows: Figure 4 shown.

[0086] Figure 4 This is the full XPS spectrum of the Ti3C2 / WO3 Schottky heterojunction photoanode in Example 1. Figure 4 The mass percentages of various elements are W: 54.05%, O: 28.39%, C: 11.97%, Ti: 5.59%. The molar ratios (M W =183.84 g·mol -1 ;M Ti =47.87 g·mol -1 ). Since the substrate is F-substituted SnO2, the mass percentage of O element is not used as a reference, and due to the operation problem of the XPS instrument itself, a part of carbon is introduced, so the carbon element is only used for peak position correction, and its mass percentage is not used as a reference value. The W element and the Ti element are both from the effective reactants, so the present invention only uses the W and Ti elements as the mass percentage reference. By calculation, n(WO3):n(Ti3C2)=0.294:0.039, so the ratio range of WO3 and Ti3C2 in the present invention is 1:(0.1-0.2).

[0087] 5. Changes in the binding energy of W 4f orbital electrons in Ti3C2 / WO3 Schottky heterojunction photoanode

[0088] X-ray photoelectron spectroscopy XPS was used to detect the changes in the W 4f orbital electron binding energy in the Ti3C2 / WO3 Schottky heterojunction photoanode in Example 1 and the WO3 photoanode in Comparative Example 1. The results are shown in Figure 5 .

[0089] Figure 5 This is the W 4f fine spectrum of the Ti3C2 / WO3 Schottky heterojunction photoanode in Example 1. Figure 5 It is known that compared with the comparative example 1WO3 photoanode W 4f 5 / 2 The orbital binding energy is 33.71 eV. Example 1 Ti3C2 / WO3 Schottky heterojunction photoanode W4f 5 / 2The orbital binding energy is 33.83 eV, and the binding energy shift is 0.12 eV. 7 / 2 The orbital binding energy is 35.86 eV. Example 1: W 4f in Ti3C2 / WO3 Schottky heterojunction photoanode 7 / 2 The orbital binding energy is 35.97 eV, and the comparison shows that there is a 0.11 eV binding energy shift.

[0090] The above results indicate that there is post-contact electron transfer between Ti3C2 and WO3 caused by the difference in work function, which supports the formation of a built-in electric field, thereby promoting the improvement of photoelectrocatalytic performance.

[0091] 6. Photoelectric performance of Schottky heterojunction photoanode

[0092] The photoelectric performance of the Ti3C2 / WO3 photoanode of Example 1 of the present invention and the WO3 photoanode of Comparative Example 1 was tested as follows:

[0093] (1) Photoelectrochemical testing was performed using a Metrohm PGSTAT302N electrochemical workstation with a classic three-electrode system. The Ti3C2 / WO3 photoanode of Example 1 and the WO3 photoanode of Comparative Example 1 were used as working electrodes to form a polarization circuit with a Pt sheet counter electrode and a measurement circuit with an Ag / AgCl reference electrode.

[0094] (2) Prepared 0.5 mol·L -1 H2SO4 is used as the electrolyte.

[0095] (3) Ti3C2 / WO3 photoanode and WO3 photoanode were processed into test areas of 1×2 cm 2 The electrode sheet is fixed on the electrode clamp, the counter electrode and the reference electrode are fixed and their contact area with the electrolyte is adjusted.

[0096] (4) Photoelectrochemical measurements were performed using a Perfectlight Microsolar 300 xenon lamp with a built-in 300 W xenon lamp.

[0097] (5) The linear sweep voltammetry (LSV) method was used to detect the photocurrent of the two groups of experiments, and the scanning rate was maintained at 0.01 V / s. The electrochemical impedance spectroscopy (EIS) method was used to measure the electrochemical reaction impedance (R ct ) and other parameters, setting the applied bias voltage to 1.23V (vs RHE), the frequency range to 1MHz to 0.1Hz, the disturbance amplitude to 10mV, and the results are shown in Figure 6 .

[0098] (6) According to the Nernst equation, ERHE =E Ag / AgCl +0.0591pH+E θ Ag / Cl The formula converts the test data (vsAg / AgCl) into the test data under the reversible hydrogen electrode (vs RHE). The results are shown in Figure 7 .

[0099] Figure 6 The JV curve of Ti3C2 / WO3 Schottky heterojunction photoanode. Figure 6 It is known that at a voltage of 1.23 V (vs RHE), the photocurrent of the Ti3C2 / WO3 heterojunction photoanode of Example 1 is up to 0.8 mA cm -2 , which is twice that of the WO3 photoanode in comparative example 1. This shows that the Ti3C2 / WO3 special-based heterojunction photoanode of the present invention can significantly improve the photoelectrocatalytic water decomposition performance of the WO3 photoanode, and also proves that the introduction of Ti3C2 can significantly improve its photoelectric conversion efficiency.

[0100] Figure 7 This is the Nyquist plot of the Ti3C2 / WO3 Schottky heterojunction photoanode. Figure 7 It is known that under a bias voltage of 1.23 V, the Rct of the Ti3C2 / WO3 heterojunction photoanode of Example 1 is about 400Ω, which is significantly lower than that of the WO3 photoanode of Comparative Example 1. The above results show that the introduction of Ti3C2 can significantly accelerate the surface charge reaction and transport process, thereby promoting the separation of photogenerated carriers and accelerating the reaction process.

[0101] The above is only a preferred embodiment of the present invention, which only specifically describes the technical principle of the present invention and is only for explaining the deep-level principle of the present invention, and should not be understood as limiting the scope of protection of the present invention. Based on the explanation here, any modification, replacement or improvement derived from the spirit and principle of the present invention, as well as other specific implementation methods of the present invention that practitioners in related fields can associate with without creative work, should be included in the scope of protection of the present invention in principle.

Claims

1. A method for preparing a Ti3C2 / WO3 Schottky heterojunction photoanode, characterized in that: The following steps are involved: (1) coating a Ti3C2 dispersion on the conductive surface of the pretreated conductive glass to obtain a conductive glass having a Ti3C2 layer on the surface; (2) coating a tungstic acid mixed solution on the Ti3C2 layer, and obtaining a conductive glass having tungstic acid / Ti3C2 on the surface after drying; (3) placing the conductive glass with tungstic acid / Ti3C2 on the surface with the conductive surface facing downward in a precursor solution for growing WO3 for hydrothermal reaction, and then washing, drying and calcining to obtain a Ti3C2 / WO3 Schottky heterojunction photoanode.

2. The method for preparing the Ti3C2 / WO3 Schottky heterojunction photoanode according to claim 1, characterized in that: In the Ti3C2 / WO3 Schottky heterojunction photoanode described in step (3), the mass ratio of WO3 to Ti3C2 is 1:(0.1-0.2); the concentration of the Ti3C2 dispersion is 1-3 mg / mL.

3. The method for preparing the Ti3C2 / WO3 Schottky heterojunction photoanode according to claim 2, characterized in that: The preparation method of the tungstic acid mixed solution is: dissolving sodium metatungstate in water, then adding citric acid and hydrochloric acid and stirring; after the preparation, the concentrations of sodium metatungstate, citric acid and hydrochloric acid are 3-5 mg / mL, 7-10 mg / mL and 0.8-1.0 mol / L.

4. The method for preparing the Ti3C2 / WO3 Schottky heterojunction photoanode according to claim 2, characterized in that: The preparation method of the precursor solution for growing WO3 is as follows: sodium metatungstate and citric acid are dissolved in water, and then hydrochloric acid is added and stirred. After the preparation is completed, the concentrations of sodium metatungstate, citric acid and hydrochloric acid in the solution are 3-5 mg / mL, 7-10 mg / mL and 0.2-0.5 mol / L.

5. The method for preparing the Ti3C2 / WO3 Schottky heterojunction photoanode according to claim 1, characterized in that: The method of coating the Ti3C2 dispersion in step (1) is multi-step spin coating, which is: first spin coating the Ti3C2 dispersion at 450-550 rpm for 18-22 seconds, and then spin coating at 2900-3100 rpm for 38-42 seconds; the method of coating the tungstic acid mixed solution in step (2) is: spin coating at 2900-3100 rpm for 18-22 seconds.

6. The method for preparing the Ti3C2 / WO3 Schottky heterojunction photoanode according to claim 1, characterized in that: The temperature of the hydrothermal reaction in step (2) is 110-130° C., and the time is 10-13 hours; the temperature of the calcination is 400-600° C., and the time is 2-5 hours; and the calcination is carried out in air.

7. The method for preparing the Ti3C2 / WO3 Schottky heterojunction photoanode according to claim 1, characterized in that: The conductive glass in step (1) is FTO conductive glass or ITO conductive glass.

8. The method for preparing the Ti3C2 / WO3 Schottky heterojunction photoanode according to claim 1, characterized in that: The pretreatment in step (1) comprises: placing the conductive glass in a mixture of deionized water and ethanol, and a mixture of 30% hydrogen peroxide and concentrated sulfuric acid in sequence for cleaning, and drying after cleaning to obtain the pretreated conductive glass.

9. A Ti3C2 / WO3 Schottky heterojunction photoanode, characterized in that: The preparation method is described in any one of claims 1 to 8.

10. The use of the Ti3C2 / WO3 Schottky heterojunction photoanode as claimed in claim 9, characterized in that: Application in photoelectrocatalytic water decomposition reaction.

Citation Information

Patent Citations

  • Tungsten trioxide nano-film with photocatalytic performance, and preparation method thereof

    CN103708559A

  • Preparation method of oxygen-deficient tungsten trioxide monohydrate / titanium carbide nano composite material

    CN111495401A

  • Preparation method and application of tungsten oxide nanowire / titanium carbide nanosheet composite material

    CN116130256A

Cited By

  • Ir-doped WO3 (at) TiN as well as preparation method and application thereof

    CN120205198A